Development of a fuel cell and energy storage system for microgrid - Mathew, Albin. (2012)
This report presents the design and implementation of a proton exchange membrane fuel cell (PEMFC) based distributed generation system integrated with energy storage device to perform load sharing with the grid. The PEMFC requires a startup time for it to reach its optimum operating voltage and also it has a slow response to load change. So when the fuel cells are connected to the microgrid, any fluctuation from the fuel cells may cause excessive variation of the voltage or frequency to the microgrid thereby degrading the quality of the grid. To recover this irregularity, lead-acid batteries and ultra-capacitors are used for energy storage and power compensation and integrated with the PEMFC. Any fluctuation from the fuel cells will be supplemented by ultra-capacitors and/or lead-acid batteries and the microgrid will not notice any disturbance generated at the DG side.